Pengembangan Aplikasi Blended Learning Di Sekolah Saat Pandemi Covid19 (Corona) - BJ, Juanda (STIKOM Tunas Bangsa Pematangsiantar, 2020)
This research aims to develop the Blended Learning application because of the COVID19 pandemic that is hitting the world. The application is built in such a way as to simplify the process of use in school learning by using the Research and Development (R&B) type of research. The development method used a model designed by Plomp with three stages of research: 1) Preliminary Research, 2) Prototype Phase, 3) Assessment Phase. The determination of the validity and practicality of the Blended Learning application is based on the validation test of experts and users, namely teachers and students, through a questionnaire, in determining the sample, using a purposive sampling technique. The results showed that the results of this development research were as follows: 1) The validity of the Blended Learning application was valid; 2) The practicality of the Blended Learning application based on user responses, namely teachers and students, was stated to be very practical. Based on the findings of this study, it is concluded that the Blended Learning application is very valid and very practical.